Prediction of potential passive exposure from commercial electronic nicotine delivery systems using exhaled breath analysis and computational fluid dynamic techniques. (5th October 2021) - Oldham, Michael J; Bailey, Patrick C; Castro, Nicolas; Lang, Qiwei; Salehi, Armin; Rostami, Ali A
Abstract: Use of computational fluid dynamic (CFD) modeling to predict temporal and spatial constituent exposure for non-electronic nicotine delivery systems (ENDS) users (passive exposure) provides a more efficient methodology compared to conducting actual exposure studies. We conducted a clinical study measuring exhaled breath concentrations of glycerin, propylene glycol, nicotine, benzoic acid, formaldehyde, acetaldehyde, acrolein, menthol and carbon monoxide from use of eight different commercial ENDS devices and a non-menthol and menthol cigarette. Because baseline adjusted levels of other constituents were not consistently above the limit of detection, the mean minimum and maximum per puff exhaled breath concentrations ( N = 20/product) of glycerin (158.7–260.9 µ g), propylene glycol (0.941–3.58 µ g), nicotine (0.10–1.06 µ g), and menthol (0.432–0.605 µ g) from use of the ENDS products were used as input parameters to predict temporal and spatial concentrations in an environmental chamber, office, restaurant, and car using different ENDS use scenarios. Among these indoor locations and ENDS use scenarios, the car with closed windows resulted in the greatest concentrations while opening the car windows produced the lowest concentrations. The CFD predicted average maximum glycerin and propylene glycol concentration ranged from 0.25 to 1068 µ g m −3 and 1.5 pg m −3 to 13.56 µ g m −3, respectively. For nicotine and menthol the CFD predicted maximum concentration ranged from 0.16 pg m −3 to 4.02 µ g m −3 and 0.068 pg m −3 to 2.43 µ g m −3, respectively. There was better agreement for CFD-predicted nicotine concentrations than glycerin and propylene glycol with published reports highlighting important experimental and computational variables. Maximum measured nicotine levels from environmental tobacco smoke in offices, restaurants, and cars exceeded our maximum average CFD predictions by 7–97 times. For all the measured exhaled breath constituents and CFD predicted constituents, except for propylene glycol and glycerin, concentrations were less from use of ENDS products compared to combustible cigarettes. NCT number: NCT04143256